The Estimation of the Prais-Houthakker Model of Equivalence Scales - Muellbauer, John (Econometrica, 1980)
Given a preference basis for the model, a household's general equivalence scale is seen to be a cost of living index relative to the reference household type defined at constant prices. A maximum likelihood estimation procedure which can be applied both to cross-section data and pooled time-series/cross-sections is derived. The lack of identification of the model is established theoretically and checked empirically on British family expenditure survey data. With prior information, e.g. a nutrition based food scale, identification can be reached but ultimately the model is rendered implausible because of its zero substitution implication and the empirical results bear this out.